Anisotropic, ultrastrong and light-transmission film designed on wheat straw. Issue 24 (6th June 2022) - Cui, Boyu; Xie, Hao; Sun, Hao; Ji, Tong; Li, Shuang; Jia, Xue; Wang, Weihong
Abstract : The highly oriented structure of wheat straw is preserved and made into a high-performance film that is expected to be used in sustainable products. Abstract : Converting wheat straw waste into a high-performance material is necessary and challenging from the perspective of "waste to wealth" and green development. This study successfully fabricated an anisotropic ultrastrong, light-transmitting, and biodegradable film from wheat straw using the top-down strategy. The resulting wheat straw film (WSF) exhibited superb tensile strength (up to 754.34 MPa), specific strength (up to 580.26 MPa cm 3 g −1 ), and toughness (up to 18.72 MJ m −3 ) due to the well-aligned cellulose nanofibers after the chemical treatment and densification. Moreover, the WSF exhibited remarkable transmittance (≈74%), haze (≈79%), and anisotropic optical properties. Considering its degradability and excellent performance, the full wheat straw-based film could be applied to sustainable biomass-based products (such as optoelectronic devices and flexible electronics).